CORRELATION BETWEEN INTEREST IN LEARNING AND MATHEMATICS LEARNING OUTCOMES TO FOURTH GRADE STUDENTS OF PUBLIC ELEMENTARY SCHOOLS IN PREMBUN SUB-DISTRICT IN ACADEMIC YEAR OF 2020/2021 - Amanda Putri Nurjanah; Suhartono Suhartono; Ratna Hidayah (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2021)
The study aimed to determine the correlation between interest in learning and mathematics learning outcomes to fourth grade students of public elementary schools in Prembun Sub-district and to measure the contribution of interest in learning on mathematics learning outcomes to fourth grade students of public elementary schools in Prembun Sub-district in academic year of 2020/2021. The research was correlational quantitative method. Sampling method was with cluster random sampling technique with the help of SPSS application. The samples were 226 fourth grade students in eleven elementary schools throughout the Prembun Sub-district. Data collection techniques used questionnaires and tests. Data Analysis used simple correlation test and adjusted R square with a significance level of 5%. The correlation test was sig = 0.000 (sig <0.05) and the result of correlation coefficient between interest in learning and mathematics learning outcomes was 0.486. It concludes that there is positive and significant correlation between interest in learning and mathematics learning outcomes to fourth grade students of public elementary schools in Prembun Sub-district in academic year of 2020/2021. Interest in learning contributes 23.69% on mathematics learning outcomes.